Circulating concentrations of vitamin D in relation to pancreatic cancer risk in European populations. Issue 6 (22nd November 2017) - van Duijnhoven, Fränzel J.B.; Jenab, Mazda; Hveem, Kristian; Siersema, Peter D.; Fedirko, Veronika; Duell, Eric J.; Kampman, Ellen; Halfweeg, Anouk; van Kranen, Henk J.; van den Ouweland, Jody M.W.; Weiderpass, Elisabete; Murphy, Neil; et al.
Abstract : Evidence from in vivo, in vitro and ecological studies are suggestive of a protective effect of vitamin D against pancreatic cancer (PC). However, this has not been confirmed by analytical epidemiological studies. We aimed to examine the association between pre‐diagnostic circulating vitamin D concentrations and PC incidence in European populations. We conducted a pooled nested case‐control study within the European Prospective Investigation into Cancer and Nutrition (EPIC) and the Nord‐Trøndelag Health Study's second survey (HUNT2) cohorts. In total, 738 primary incident PC cases (EPIC n  = 626; HUNT2 n  = 112; median follow‐up = 6.9 years) were matched to 738 controls. Vitamin D [25(OH)D2 and 25(OH)D3 combined] concentrations were determined using isotope‐dilution liquid chromatography‐tandem mass spectrometry. Conditional logistic regression models with adjustments for body mass index and smoking habits were used to estimate incidence rate ratios (IRRs) and 95% confidence intervals (95%CI). Compared with a reference category of >50 to 75 nmol/L vitamin D, the IRRs (95% CIs) were 0.71 (0.42–1.20); 0.94 (0.72–1.22); 1.12 (0.82–1.53) and 1.26 (0.79–2.01) for clinically pre‐defined categories of ≤25; >25 to 50; >75 to 100; and >100 nmol/L vitamin D, respectively ( p for trend = 0.09). Corresponding analyses by quintiles of season‐standardized vitamin D concentrations also did not reveal associations with PC risk ( p for trend = 0.23). Although these findings among participants from the largest combination of European cohort studies to date show increasing effect estimates of PC risk with increasing pre‐diagnostic concentrations of vitamin D, they are not statistically significant. Abstract : What's new? Living at lower latitude and increased ultraviolet light exposure are inversely correlated with pancreatic cancer (PC) risk, supporting a model where vitamin D may protect from this devastating cancer. Here, the authors performed the largest combination of European studies to date and find that higher vitamin D concentrations are not associated with a lower risk of PC. They recommend caution before guidelines to increase vitamin D concentrations for the prevention of cancer can be recommended.